Real-time effects of central bank interventions in the Euro market - Rasmus Fatum; Jesper Pedersen (Danmarks Nationalbank, 2007)
This paper investigates the real-time effects of foreign exchange intervention using official intraday intervention data provided by the Danish central bank. Denmark is currently pursuing an active intervention policy under the provisions of the Exchange Rate Mechanism (ERM II) and intervenes on a discretionary basis when considered necessary. Prior participation in ERM II is a requirement for adoption of the Euro. Therefore, our study is of particular relevance for the new European Union member states that are either currently participating in ERM II or expected to do so at a later date as well as for Denmark. Our analysis employs the twostep weighted least squares estimation procedure of Andersen, Bollerslev, Diebold and Vega (2003) and an array of robustness tests. We find that intervention exerts a statistically and economically significant influence on exchange rate returns when the direction of intervention is consistent with fundamentals and intervention is carried out during a period of high exchange rate volatility. We also show that the exchange rate does not adjust instantaneously to the unannounced and discretionary interventions under study. We conclude that intervention can be an important short-term policy instrument for exchange rate management.
Keywords: D53; E58; F31; G15; 330; Foreign Exchange Intervention; Intraday Data; ERM II; Zentralbank; Wechselkurspolitik; Europäischer Währungsverbund; Eurozone; Wirkungsanalyse; Ökonometrisches Modell; Dänemark